Health financing in Malawi: Evidence from National Health Accounts - Zawaira Felicitas; Kirigia Joses; Walker Oladapo; Zere Eyob; Magombo Francis; Kataika Edward (BMC, 2010)
Abstract Background National health accounts provide useful information to understand the functioning of a health financing system. This article attempts to present a profile of the health system financing in Malawi using data from NHA. It specifically attempts to document the health financing situation in the country and proposes recommendations relevant for developing a comprehensive health financing policy and strategic plan. Methods Data from three rounds of national health accounts covering the Financial Years 1998/1999 to 2005/2006 was used to describe the flow of funds and their uses in the health system. Analysis was performed in line with the various NHA entities and health system financing functions. Results The total health expenditure per capita increased from US$ 12 in 1998/1999 to US$25 in 2005/2006. In 2005/2006 public, external and private contributions to the total health expenditure were 21.6%, 60.7% and 18.2% respectively. The country had not met the Abuja of allocating at least 15% of national budget on health. The percentage of total health expenditure from households' direct out-of-pocket payments decreased from 26% in 1998/99 to 12.1% in 2005/2006. Conclusion There is a need to increase government contribution to the total health expenditure to at least the levels of the Abuja Declaration of 15% of the national budget. In addition, the country urgently needs to develop and implement a prepaid health financing system within a comprehensive health financing policy and strategy with a view to assuring universal access to essential health services for all citizens.